INFERTILITY DETERMINANTS AMONG MARRIED COUPLES IN COIMBATORE DISTRICT - Shankaranarayanan M N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study was aimed at determining the factors associated with infertility among married couples in Coimbatore district. The relationship between infertility and psychological stress is complex. On the one hand, infertile couples are subject to greater stress and have a greater risk of developing psychological disorders compared with normal, healthy couples. On the other hand, high levels of psychological distress have been indicated to increase infertility. The study has given four factors namely, Lifestyle, Physiological, Health Risk Factors in Men and Health Risk Factors in Women using Factor Analysis. Therefore, the research team suggests a couple turn to the assessment and treatment of marital dissatisfaction in Infertile Couple. Sexuality is paradoxical-sexual dysfunction, especially lowered desire, and it increases as infertility problems continue. In addition, males feel more shameful, but deny their infertility and do not seek psychological support. Thus, comprehensive psycho-bio-social approach in couple therapy and counselling can improve sexual, marital satisfaction and quality of life in infertile couple.